Holding companies as beneficial owners and intermediaries of dividends - Oskar Winnicki (Prawo Budżetowe Państwa i Samorządu)
Many issues in an application of a tax regulation concerning a withhold tax appeared with an entry into force of an amendment to the Corporate Income Tax Act from 2019. Legal definition of a beneficial owner has generated numerous problems in applying tax exemption by holding companies, due to disputes addressing a question if holding companies fulfils requirements of a definition of “actual economic activity”. This definition (which is included in Article 24a(18) of Corporate Income Tax Act) is essential to use tax exemption from Article 22(4) of Corporate Income Tax Act. The article is focused on regulations on an exemption from withholding tax applied in relation to holding companies. It is claimed that holding companies are able to fulfil, in broaden meaning, the definition of the beneficial owner. The second part of the article focuses on the possibility of using a “look through approach” when a holding company is only an intermediary. This view is verified in particular from a perspective of newly published explanations from 28 September 2023 of the Ministry of Finance.